Neddylation of protein, a new strategy of protein post-translational modification for targeted treatment of central nervous system diseases - Wu, Qian; Geng, Ziang; Lu, Jun; Wang, Shisong; Yu, Zhongxue; Wang, Siqi; Ren, Xiaolin; Guan, Shu; Liu, Tiancong; Zhu, Chen (Frontiers in Neuroscience, 2024)
Neddylation, a type of protein post-translational modification that links the ubiquitin-like protein NEDD8 to substrate proteins, can be involved in various significant cellular processes and generate multiple biological effects. Currently, the best-characterized substrates of neddylation are the Cullin protein family, which is the core subunit of the Cullin-RING E3 ubiquitin ligase complex and controls many important biological processes by promoting ubiquitination and subsequent degradation of various key regulatory proteins. The normal or abnormal process of protein neddylation in the central nervous system can lead to a series of occurrences of normal functions and the development of diseases, providing an attractive, reasonable, and effective targeted therapeutic strategy. Therefore, this study reviews the phenomenon of neddylation in the central nervous system and summarizes the corresponding substrates. Finally, we provide a detailed description of neddylation involved in CNS diseases and treatment methods that may be used to regulate neddylation for the treatment of related diseases.